Prevalence of SARS-CoV-2 infection and impact of the COVID-19 pandemic in avocado farmworkers from Mexico - Armendáriz-Arnez, Cynthia; Tamayo-Ortiz, Marcela; Mora-Ardila, Francisco; Rodríguez-Barrena, María Esther; Barros-Sierra, David; Castillo, Federico; Sánchez-Vargas, Armando; Lopez-Carr, David; Deardorff, Julianna; Eskenazi, Brenda; Mora, Ana M. (Frontiers in Public Health, 2023)
Introduction The COVID-19 pandemic disproportionately affected farmworkers in the United States and Europe, leading to increased morbidity and mortality. However, little is known about the specific impact of the pandemic on agriculture and food production workers in low- and middle-income countries. This study aimed to investigate the prevalence of SARS-CoV-2 infection and assess the mental health and economic consequences of the COVID-19 pandemic among avocado farmworkers in Michoacan, Mexico. Methods We conducted a cross-sectional study of adult farmworkers (n = 395) in May 2021. We collected survey data, nasal swabs and saliva samples for SARS-CoV-2 RNA detection, and blood samples for immunoglobulin G (IgG) reactivity measurements. Results None of the farmworkers tested positive for SARS-CoV-2 RNA. However, among unvaccinated farmworkers (n = 336, 85%), approximately one-third (33%) showed evidence of past infection (positive for IgG against SARS-CoV-2). Unvaccinated farmworkers who lived with other farmworkers (aRR = 1.55; 95% CI: 1.05, 2.05), had ever lived with someone with COVID-19 (aRR = 1.82; 95% CI: 1.22, 2.43), and who had diabetes (aRR = 2.19; 95% CI: 1.53, 2.85) had a higher risk of testing IgG-positive for SARS-CoV-2 infection. In contrast, unvaccinated farmworkers living in more rural areas (outside of Tingambato or Uruapan) (aRR = 0.71; 95% CI: 0.46, 0.96) or cooking with wood-burning stove (aRR = 0.75; 95% CI: 0.55, 0.96) had a lower risk of IgG-positivity. Moreover, 66% of farmworkers reported a negative impact of the pandemic on their lives, 29% reported experiencing food insecurity and difficulty paying bills, and 10% reported depression or anxiety symptoms. Conclusion The COVID-19 pandemic has significantly affected the mental health and financial well-being of avocado farmworkers. Consequently, the implementation of interventions and prevention efforts, such as providing mental health support and food assistance services, is imperative.